HUBUNGAN KEPERCAYAAN DIRI DAN DUKUNGAN TEMAN SEBAYA DENGAN JENIS PERILAKU BULLYING DI MTsN LAWANG MANDAHILING KECAMATAN SALIMPAUNG TAHUN 2017 - Marizki Putri (Menara Ilmu, 2018)
Violent behavior today often occurs in the social life of teenagers, especially in the schoolenvironment. Bullying is a form of violent behavior in which psychological or physical coercionexists against a person or group of weaker persons by a stronger person or someone who has thepower to do anything to the victim. The victim also perceives himself as a weak, powerless partyalways threatened by bully. The purpose of this study is to see related to the type of Bullyingbehavior in MTsN Mandahiliang Salimpaung Subdistrict Tanah Datar in 2017. The design of thisresearch is a cross sectional approach. Independent variable is Relationship type of Bullyingbehavior and dependent variable is kind of Bullying behavior. Sampling technique in this researchby using random sampling technique, with the number of respondents 95 students. The results ofstatistical tests show there is a relationship between self-confidence and peers with the type ofBullying behavior. The implications of the research results show that the types of Bullying behaviorhave an important role in Bullying behavior, and for other researchers can be used as input andcomparison for further research